2014
DOI: 10.1016/j.mspro.2014.07.209
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Machining Performances Using MRA, GMDH and Artificial Neural Network in Wire EDM of EN-31

Abstract: Wire Electrical Discharge Machining (WEDM) is a specialized thermal machining process capable of accurately machining parts with varying hardness or complex shapes, which have sharp edges that are very difficult to be machined by the main stream machining processes. This study outlines the development of model and its application to estimation of machining performances using Multiple Regression Analysis (MRA), Group Method Data Handling Technique (GMDH) and Artificial Neural Network (ANN). Experimentation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The Taguchi's method of creating the DOE is mostly preferred due to the fact that the number of experiments is the least in this method [10]. In the literatures [11][12][13][14], the authors showed that peak current (I.P. ), pulse on time (T on ), pulse off time (T off ), servo voltage (SV) and percentage of B 4 C (% B 4 C) significantly effects the material removal rate (MRR), surface roughness R a and R z and kerf thickness ( ) while machining Al5083/B 4 C composite by WEDM.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The Taguchi's method of creating the DOE is mostly preferred due to the fact that the number of experiments is the least in this method [10]. In the literatures [11][12][13][14], the authors showed that peak current (I.P. ), pulse on time (T on ), pulse off time (T off ), servo voltage (SV) and percentage of B 4 C (% B 4 C) significantly effects the material removal rate (MRR), surface roughness R a and R z and kerf thickness ( ) while machining Al5083/B 4 C composite by WEDM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Artificial Neural Network (ANN) is a better and developed way of modelling the performance measures. In [12], ANN is used to develop a mathematical model for predicting MRR and surface roughness. In [15], Elman-Based layer recurrent network for accurately predicting the performance measures of WEDM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was observed that pulse-on time and peak current were the most significant parameters. Ugrasen et al (2014) developed a multi regression model and group method data handling technique for wire electric discharge machining process and estimated the best fit of data for SR and MRR. Kumar et al (2015) proposed a combined model Taguchi’s method and gray relational analysis (GRA) to optimize process parameters of WEDM for machining of Aluminium 6351.…”
Section: Introductionmentioning
confidence: 99%
“…Mohanty and Nayak [25] has applied Taguchi method to optimize the MRR and SR as response parameters. Ugrasen et al [26] developed a model to estimate the optimal machining performances of WEDM process using multiple regression analysis (MRA), group method data handling technique (GMDH) and ANN in machining of EN31 so as to obtain the optimal responses of accuracy, surface roughness and volumetric material removal rate. Diyaley et al [27] has applied the combination of preference selection index (PSI) and TOPSIS to obtain the parametric combination of WEDM process while machining of EN31 steel.…”
Section: Introductionmentioning
confidence: 99%